An application of Extended Normalisation Process Theory in a randomised controlled trial of a complex social intervention: Process evaluation of the Strengthening Families Programme (10-14) in Wales, UK - Jeremy Segrott; Simon Murphy; Heather Rothwell; Jonathan Scourfield; David Foxcroft; David Gillespie; Jo Holliday; Kerenza Hood; Claire Hurlow; Sarah Morgan-Trimmer; Ceri Phillips; Hayley Reed; et al. (Elsevier, 2017)
Purpose: Process evaluations generate important data on the extent to which interventions are delivered as intended. However, the tendency to focus only on assessment of pre-specified structural aspects of fidelity has been criticised for paying insufficient attention to implementation processes and how intervention-context interactions influence programme delivery. This paper reports findings from a process evaluation nested within a randomised controlled trial of the Strengthening Families Programme 10-14 (SFP 10-14) in Wales, UK. It uses Extended Normalisation Process Theory to theorise how interaction between SFP 10-14 and local delivery systems - particularly practitioner commitment/capability and organisational capacity - influenced delivery of intended programme activities: fidelity (adherence to SFP 10-14 content and implementation requirements); dose delivered; dose received (participant engagement); participant recruitment and reach (intervention attendance). Methods: A mixed methods design was utilised. Fidelity assessment sheets (completed by practitioners), structured observation by researchers, and routine data were used to assess: adherence to programme content; staffing numbers and consistency; recruitment/retention; and group size and composition. Interviews with practitioners explored implementation processes and context. Results: Adherence to programme content was high - with some variation, linked to practitioner commitment to, and understanding of, the intervention's content and mechanisms. Variation in adherence rates was associated with the extent to which multi-agency delivery team planning meetings were held. Recruitment challenges meant that targets for group size/composition were not always met, but did not affect adherence levels or family engagement. Targets for staffing numbers and consistency were achieved, though capacity within multi-agency networks reduced over time. Conclusions: Extended Normalisation Process Theory provided a useful framework for assessing implementation and explaining variation by examining intervention-context interactions. Findings highlight the need for process evaluations to consider both the structural and process components of implementation to explain whether programme activities are delivered as intended and why.